Penerapan Metode K-Means Clustering dalam Klasterisasi Pemilihan Pasir Sesuai SNI - Ladyka Febby Olivia; Billy Hendrik (Lembaga Pengembangan Kinerja Dosen, 2023)
Development is a government effort to develop a prosperous society. The house is a basic need that is met by every human being as a decent place to live, which is not only for a place to rest and shelter. The method used is clustering with the K-Means algorithm against 8 sand sample data. The results obtained from the data mining process use SPSS software that produces very good, good, and not good.